PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PT PERTAMINA (PERSERO) PAREPARE - Idrus, Irwan; Anugrah, Ryan (Universitas Muhammadiyah Parepare, 2020)
This research aims to find out if occupational safety and health have a significant impact on employee productivity in PT. Pertamina (Persero) Terminal BBM Parepare. The data used in this study was obtained through questionnaires, observations and in-person interviews with employees. The analysis technique used is multiple regression analysis using SPSS program. From this study can be concluded based on statistical tests (t test and F test) that work safety variables have a significant effect on employee productivity; work health has a significant impact on employee productivity; safety and health simultaneously affect employee productivity. From the results of this study obtained a determination coefficient value (R Square) of 0.515 this shows that the contribution of the influence of independent variables namely occupational safety and health to employee productivity is 51.5%.